Effectiveness of Retrieval Practice Learning Strategy in the Memory Storage Process to Improve Students Learning Outcomes on Cell Structure and Bioprocesses - Adella Gusti Alviani; Ermayanti; Lucia Maria Santoso (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the implementation of retrieval practice learning strategies in students learning outcomes on the material Structure and Cell Bioprocesses. The research method used was quasi experimental. The research subject were students of XI IPA, public senior high school in Palembang. The research instruments used were test questions and observation sheets. Learning outcomes data were analyzed with the independent sample t-test on the Statistical Program for Social Science 26 (SPSS version 26). The results showed that both the experimental class and the control class experienced an increase in learning outcomes from the initial test results. The average learning outcomes of the experimental class (retrieval practice) (41.11) are proven to be higher than the control class (32.24). In addition, the N-gain obtained by the experimental class is 0.05 and the control class is 0.10 which is in the low category. Moreover, the results also show that the experimental and control class students have not reached the master learning. These results show that both experimental and control classes get an increase in learning outcomes that are not optimal. However, the retrieval practice learning strategy still provides benefits for improving student learning outcomes.